Passivity-based Control of Voltage Source Converter Based On Mixed Sensitivity H∞. Issue 1 (February 2021) - Li, Yaxin; Yang, Jie; Fang, Rengcun; Xu, Hanping; Yang, Ruixi; Zhang, Chengbiao
Abstract: Considering the uncertainty of the control object, this paper aims to design the passivity-based control of voltage source converter based on mixed sensitivity H∞. Firstly, the plant model of VSC converter has been deduced and proved by simulation. Then the controllable of plant has been analyzed. Furthermore, based on mixed sensitivity H∞ theory, the performance weight function and passivity-based control have been designed. Finally, proved by simulation comparison, this control has more accurate and robust dynamic performance than the traditional ac voltage control.